A Contrastive Study of Indonesian and American Compliments (A Socio - Pragmatic Approach) - Rusdin, Rusdin (NUANSA, 2016)
The purpose of this study is to identify and classify the types of topic of compliments, the functions and the compliment responses conveyed by the Indonesian and American. The data in this study were taken from each of the two films, namely; "Kapan Kawin?" and âGaruda di Dadaku" from the Indonesians and âModern Family "and Pixels" from the Americans. The method used in analyzing this research is descriptive qualitative and quantitative method. The data for this study were collected using ethnographic analyzing by Manes and Wolfson (1980) and Janet Holmes (1986). The analysis is exploring the features of distribution of giving compliments, functions, and responses for Indonesian and American. The discussion of data begins with watching the movie, writing the transcripts dialogs that contains of compliments and compliment responses used in the movie. The result of this study shows that there is a difference equation signs and similarity of compliment and compliment responses are used by the people of Indonesia and American. In which can be seen from the percentage of the use of compliments and compliment responses strategy used by both countries. The compliment topics used by Indonesian and American complimenters show a strong preference for ability/skill and personality over appearance and possessions. In the tables shown that American used 225 compliments and compliment responses while Indonesian used 146 compliments and compliment responses. Americans are more often give compliments and compliment responses rather than Indonesian. It was clear evident that generally Americans are more frequently to produce compliments and compliment responses rather than Indonesian. This different can be cause of the culture and habit that influence both of the countries. The researcher hopes that this research gives a contribution to the teachers and students in teaching and learning of speech act of compliments especially in terms of sociolinguistic.